POLITICAL POWER COMPONENT OF PUBLIC POLICY : THEORETICAL BASIS - Чальцева, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Political power as a component of public policy can be viewed through a variety of methodological approaches, but before modern scholars who study the transitional system, worth two difficult problems. The first - an association of power theories and theories of public policy. The second - the adaptation of existing methodological approaches to national contexts and the need to build new theories.